Mathematical modeling of physical and chemical processes in the combustion chamber of the boiler BKZ-420 - Асқарова, Ә.С.; Бөлегеновa С.Ә.; Максимов, В.Ю.; Усербaев Б.Ж.; Нахипова, Ф. (Хабаршы. Физика сериясы, 2016)
This work is dedicated to the study of physical and chemical processes during burning solid oil in the dust form in the combustion chamber of industrial boilers «BKZ-420». During the research of physical and chemical processes, aside from the mathematical models, 2D and 3D models were examined as well. Along with this, considering kinetics of chemical reactions of Navier-Stokes three-dimensional equations, thermal and aerodynamic characteristics of flows were defined within the burner, the exit, along the longitudinal cuts, which in the combustion chamber take place in the basics of turbulence equations and diphase of environment. Methods of decreasing the levels of environment contamination and maintaining them in the normal condition are being considered. Obtained results of experimental research were compared to the results of the main experiment, taken from TES center.